Analysis of Historical Learning on Attitude and Interests of MA Al-Muhajirin Students - Agus Susilo; Isbandiyah Isbandiyah (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
Learning history is now very vital at the high school level. The presence of the 2013 curriculum makes assessment in learning history not only seen from the learning outcomes obtained by students at the end of the semester, but also the process of attending school activities. The purpose of writing this scientific article is to analyze the history of learning towards the attitudes and interests of MA Al-Muhajirin students. In writing this scientific article, the writer is based on observational aspects that exist in MA Al-Muhajirin. From the author's observations that are supported by references that support the data obtained to be a reference writing this scientific article. discussion related to the analysis of historical learning on the attitudes and interests of MA Al-Muhajirin's students is known that the values of historical learning are very important in shaping the attitude of Al Muhajirin's students. How the history teacher makes it important and arouse students' interest in participating in history learning. Learning history that is well followed and always innovating will produce a good new nuance. His conclusion by following history learning well and the ability to innovate history teachers will add insight and knowledge to the development of students' attitudes and interests in learning.